Migrasi Penduduk Kerinchi Sumatera Ke Semenanjung Tanah Melayu: Migration of the Population of Kerinchi Sumatra to the Malay Peninsula - Zakaria, Aisyah; Ab Halim, Asyiqin (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2024)
This article discusses the migration of the Kerinchi people of Sumatra to the Malay Peninsula. The Kerinchi community originally existed in Indonesia that started migrating to Malaysia long ago. There are many village constructions for the Kerinchi community in Malaysia, including Kampung Kerinchi, Kampung Abdullah Hukum and so on. This article will emphasize two things, which is to study the concept of migration and identify the migration of the Kerinchi community to Malaysia and its factors. The research data is taken through the documentation method which is obtained from books and databases of scientific articles. In addition, the data obtained will be analyzed through inductive and deductive methods. With this it can be stated that this migration has been happening for quite a long time and this is driven by driving factors from the country of origin and pulling factors from the destination country such as more economic opportunities, the atmosphere of the country and the facilities available. For the Kerinchi community, this migration occurs due to economic factors and mutual encouragement where those who live or work in Malaysia invite their family or friends in the country of origin to migrate to Malaysia.